Nurturing royal service: UiTM's F&B training at Istana Arau / Azlan Salim … [et al.] - Salim, Azlan; Mohamad Saber, Joesri; Bahari, Khairil Anuar; Mat Noor, Syuhirdy (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2025)
On the 26th and 27th of June 2024, with immense pride, we, the lecturers from the Faculty of Hotel and Tourism Management (FPHP) were invited by the Office of His Royal Highness, the Tuanku Raja of Perlis, to provide training to the dining officers of Istana Arau. Alhamdulillah, the Food and Beverage Service team from FPHP UiTMCPP successfully fulfilled the entrusted responsibility of training the officers of Istana Arau, Perlis. This comprehensive theoretical and hands-on training aimed to elevate the existing knowledge and skills of the dining officers of Istana Arau. The sessions delved into the latest developments and trends in food and beverage service, while also honing the fundamental skills essential for a royal dining attendant.